Wnt signaling and polarity in freshwater sponges - Windsor Reid, Pamela J. (BMC Evol Biol, 2018)
BACKGROUND: The Wnt signaling pathway is uniquely metazoan and used in many processes during development, including the formation of polarity and body axes. In sponges, one of the earliest diverging animal groups, Wnt pathway genes have diverse expression patterns in different groups including along the anterior-posterior axis of two sponge larvae, and in the osculum and ostia of others. We studied the function of Wnt signaling and body polarity formation through expression, knockdown, and larval manipulation in several freshwater sponge species. RESULTS: Sponge Wnts fall into sponge-specific and sponge-class specific subfamilies of Wnt proteins. Notably Wnt genes were not found in transcriptomes of the glass sponge Aphrocallistes vastus. Wnt and its signaling genes were expressed in archaeocytes of the mesohyl throughout developing freshwater sponges. Osculum formation was enhanced by GSK3 knockdown, and Wnt antagonists inhibited both osculum development and regeneration. Using dye tracking we found that the posterior poles of freshwater sponge larvae give rise to tissue that will form the osculum following metamorphosis. CONCLUSIONS: Together the data indicate that while components of canonical Wnt signaling may be used in development and maintenance of osculum tissue, it is likely that Wnt signaling itself occurs between individual cells rather than whole tissues or structures in freshwater sponges. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-018-1118-0) contains supplementary material, which is available to authorized users.